Use of DNA microarray chips for the rapid detection of Mycobacterium tuberculosis resistance to rifampicin and isoniazid - Tang, Peijun (Exp Ther Med, 2017)
The objective of the present study was to evaluate the potential development of DNA microarray chips to detect rifampicin (RFP) and isoniazid (INH) resistance in Mycobacterium tuberculosis (MTB), using samples from clinical tuberculosis (TB) patients in Soochow City, China. The sputum samples of 42 patients with TB in the Affiliated Hospital of Infectious Diseases of Soochow University (Soochow, China) were collected. The conventional Lowenstein-Jensen culture medium (Gold Standard) was used to assess drug sensitivity using the absolute concentration method. GeeDom MTB drug detection kits were also used to create a DNA microarray chip and examine the RFP-resistance associated gene mutation points rpoB-RRDR 511, 513, 516, 526, 531 and 533, and the INH-resistance associated gene mutation points katG315 and inhA-15 of the sputum samples. Compared with the results from the absolute concentration method, the susceptibility and specificity of RFP sensitivity detected by the DNA microarray chip were 92.8 and 93.8%, respectively. The susceptibility and specificity of INH sensitivity detected were 66.7 and 81%, respectively. The rpoB-RRDR 526, 531 mutations were the primary causes of MTB RFP resistance and the katG315 mutation was the primary cause of INH resistance. The detection of rpoB and katG gene mutation points by a DNA microarray chip may be used as a rapid, accurate and bulk clinical detection method for RFP and INH resistance in MTB. This is very valuable for the control of TB epidemics.